The estimation of blood galactose using a glucose oxidase-catalase reagent - Bowden, C. H. (1963)
The removal of the blood glucose by yeast fermentation in a conventional blood galactose method is replaced by an enzymic reaction using a glucose oxidase-catalase reagent. The method can be readily modified to suit a variety of blood sugar estimation methods.